2016
DOI: 10.1159/000447822
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroprotective Effect of Puerarin in Acute Spinal Cord Injury Rats

Abstract: Background: Acute spinal cord injury (SCI) leads to permanent disabilities. This study evaluated the neuroprotective effect of puerarin, a natural extract, in a rat model of SCI. Methods: Acute SCI models were established in rats using a modified Allen's method. Locomotor function was evaluated using the BBB test. The histological changes in the spinal cord were observed by H&E staining. Neuron survival and glial cells activation were evaluated by immunostaining. ELISA and realtime PCR were used to measure sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 52 publications
0
35
0
Order By: Relevance
“…After the spinal cord was fixed, the surrounding area of T10 was considered the injury region. The T9-T10 spinal cord was injured with modified Allen’s method [15] in the saline control, BMSCs and BMSCs + TNF-α groups, and the rat model of SCI was successfully established. The wound was washed and dusted with an appropriate amount of penicillin powder on the surface.…”
Section: Methodsmentioning
confidence: 99%
“…After the spinal cord was fixed, the surrounding area of T10 was considered the injury region. The T9-T10 spinal cord was injured with modified Allen’s method [15] in the saline control, BMSCs and BMSCs + TNF-α groups, and the rat model of SCI was successfully established. The wound was washed and dusted with an appropriate amount of penicillin powder on the surface.…”
Section: Methodsmentioning
confidence: 99%
“…Countless laboratory studies have demonstrated potential therapeutic options, including traditional Chinese herbs [18, 19], but none has shown clinical efficacy [20]. Even the most promising candidate, prednisone, remains controversial [21-23].…”
Section: Discussionmentioning
confidence: 99%
“…SCI is a common central nervous system condition without an effective therapeutic strategy. The secondary injury, particularly neuronal apoptosis, leads to severe disability [1,6,47]. No therapy can completely improve the motor and sensory capabilities lost after SCI [48].…”
Section: Discussionmentioning
confidence: 99%
“…The number of people living with SCI around the world is estimated to be about 3 million, with 130, 000 new patients reported each year [3,4]. After the initial traumatic insult, secondary injury mechanisms begin, including neuronal apoptosis, edema, oxidative stress, vascular dysfunction, glutamate-mediated excitotoxicity, and inflammation, which result in continued and extensive tissue damage [1,[5][6][7]. Multiple studies in recent decades have demonstrated that neuronal apoptosis occurs in the early stage of SCI, resulting in massive neuronal loss [8][9][10].…”
Section: Introductionmentioning
confidence: 99%